A curcumin–resveratrol–carnosic acid complex mitigates brain–gut axis disruption in a rodent model of repeated mild traumatic brain injury - Mohind C Mohan; Anjana A S; Deepa Azhchath Vasu; Yadukrishnan M B; Aneesa P A; Tara Sudhadevi; Krishnakumar I M; Baby Chakrapani P S (Metabolic Brain Disease, 2026)

Nrf2 signaling in bone health: unlocking new avenues for osteoporosis management - Mitali P. Lavhale; Satish K. Mandlik; Vaibhav M. Shinde; Deepa S. Mandlik (Inflammopharmacology, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Biological Decontamination of Mycotoxigenic Fusarium verticillioides Using Lactiplantibacillus plantarum MYSN128 Isolated from Traditional Vellappam: Implications for Food Safety and Global Mycotoxin Management - G. Adithi; Rakesh Somashekaraiah; B. Shruthi; S. Divyashree; N. Deepa; P. R. Vanitha; R. Vasundaradevi; B. V. Deepthi; M. Y. Sreenivasa (Current Microbiology, 2025)

Fertile grounds: exploring male sterility in cotton and its marker development - V. Deepa Dharsini; A. Subramanian; N. Premalatha; N. Manikanda Boopathi; M. Djanaguiraman; V. P. Santhanakrishnan (Molecular Biology Reports, 2024)

Diagnostic efficacy of urinary neutrophil gelatinase-associated lipocalin and kidney injury molecule-1 for early detection of acute kidney injury in dogs with leptospirosis or babesiosis - M. Asma Idress; P. M. Deepa; R. L. Rathish; K. Vinodkumar; M. Pradeep (Veterinary Research Communications, 2024)

Lipoarabinomannan (LAM)—a potential biomarker for the diagnosis of tuberculosis from the urine of infected elephants - Ranjini Manuel; P. M. Deepa; Ashok Unni; Lijo John; Deepa C.K (European Journal of Wildlife Research, 2023)

Galactosylgalactosylxylosylprotein 3-beta-glucuronosyltransferase—a potent biomarker for the diagnosis of tuberculosis in elephants - Ranjini Manuel; P. M. Deepa; R. U. Ashok; Rajeshkumar; K. Vijayakumar; K. Karthiayini; A. Janus (European Journal of Wildlife Research, 2022)

Rapid assessment of insect pollination services to inform decision‐making - Fabrizia Ratto; Tom D. Breeze; Lorna J. Cole; Michael P. D. Garratt; David Kleijn; Bill Kunin; Denis Michez; Rory O'Connor; Jeff Ollerton; Robert J. Paxton; Guy M. Poppy; Simon G. Potts; et al. (Conservation Biology, 2022)
Pollinator declines have prompted efforts to assess how land‐use change affects insect pollinators and pollination services in agricultural landscapes. Yet many tools to measure insect pollination services require substantial landscape‐scale data and technical expertise. In expert workshops, 3 straightforward methods (desk‐based method, field survey, and empirical manipulation with exclusion experiments) for rapid insect pollination assessment at site scale were developed to provide an adaptable framework that is accessible to nonspecialist with limited resources. These methods were designed for TESSA (Toolkit for Ecosystem Service Site‐Based Assessment) and allow comparative assessment of pollination services at a site of conservation interest and in its most plausible alternative state (e.g., converted to agricultural land). We applied the methods at a nature reserve in the United Kingdom to estimate the value of insect pollination services provided by the reserve. The economic value of pollination services provided by the reserve ranged from US$6163 to US$11,546/year. The conversion of the reserve to arable land would provide no insect pollination services and a net annual benefit from insect‐pollinated crop production of approximately $1542/year (US$24∙ha –1 ∙year –1 ). The methods had wide applicability and were readily adapted to different insect‐pollinated crops: rape ( Brassica napus ) and beans ( Vicia faba ) crops. All methods were rapidly employed under a low budget. The relatively less robust methods that required fewer resources yielded higher estimates of annual insect pollination benefit.

Inferring ecological strategies of Psenopsis spp. (Teleostei: Centrolophidae) inhabiting Indian waters from morphological features - K. V. Aneesh Kumar; M. P. Rajeeshkumar; M. Hashim; K. P. Deepa; J. L. Otero-Ferrer; N. Saravanane; Sujitha Thomas; K. K. Bineesh; V. M. Tuset (Marine Biology Research, 2022)

Near reef abundance and on–offshore distribution of tuna larvae around Minicoy Island in Lakshadweep Sea, India - K. V. Aneesh Kumar; K. P. Deepa; M. M. Muhammed Rafeeq; G. Sree Renjima; Hashim Manjebrayakath; B. R. Smitha; N. Saravanane; M. P. Prabhakaran; V. N. Sanjeevan; M. Sudhakar (Marine Biology Research, 2020)

Occurrence of a rare gigantic sized deep-sea cod Lepidion inosimae (Günther, 1887) in the Northwestern Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2017)

First record of deep-sea gigantic pycnogonid Colossendeis colossea Wilson, 1881 from the Western Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2016)

The effect of flavanol-rich cocoa on cerebral perfusion in healthy older adults during conscious resting state: a placebo controlled, crossover, acute trial - Daniel J. Lamport; Deepa Pal; Christina Moutsiana; David T. Field; Claire M. Williams; Jeremy P. E. Spencer; Laurie T. Butler (Psychopharmacology, 2015)

Genotyping-by-sequencing based intra-specific genetic map refines a ‘‘QTL-hotspot” region for drought tolerance in chickpea - Deepa Jaganathan; Mahendar Thudi; Sandip Kale; Sarwar Azam; Manish Roorkiwal; Pooran M. Gaur; P B Kavi Kishor; Henry Nguyen; Tim Sutton; Rajeev K. Varshney (Molecular Genetics and Genomics, 2015)

Genetic dissection of drought tolerance in chickpea (Cicer arietinum L.) - Rajeev K. Varshney; Mahendar Thudi; Spurthi N. Nayak; Pooran M. Gaur; Junichi Kashiwagi; Lakshmanan Krishnamurthy; Deepa Jaganathan; Jahnavi Koppolu; Abhishek Bohra; Shailesh Tripathi; Abhishek Rathore; Aravind K. Jukanti; et al. (Theoretical and Applied Genetics, 2014)

A Model Study on Understanding the Influence of Arabian Sea Mini Warm Pool on Monsoon Onset Vortex Formation - R. Deepa; C. Gnanaseelan; M. Deshpande; P. S. Salvekar (Pure and Applied Geophysics, 2012)

Accumulation of mercury and other heavy metals in edible fishes of Cochin backwaters, Southwest India - Mahesh Mohan; M. Deepa; E. V. Ramasamy; A. P. Thomas (Environmental Monitoring and Assessment, 2012)

A novel association of a polymorphism in the first intron of adiponectin gene with type 2 diabetes, obesity and hypoadiponectinemia in Asian Indians - Karani S. Vimaleswaran; Venkatesan Radha; Kandaswamy Ramya; Hunsur Narayan Sathish Babu; Nageshappa Savitha; Venkataramaiah Roopa; Dhar Monalisa; Raj Deepa; Saurabh Ghosh; Partha P. Majumder; M. R. Sathyanarayana Rao; Viswanathan Mohan (Human Genetics, 2008)